2019
DOI: 10.1111/1365-2656.13118
|View full text |Cite
|
Sign up to set email alerts
|

Low fitness at low latitudes: Wintering in the tropics increases migratory delays and mortality rates in an Arctic breeding shorebird

Abstract: Evolutionary theories of seasonal migration generally assume that the costs of longer migrations are balanced by benefits at the non‐breeding destinations. We tested, and rejected, the null hypothesis of equal survival and timing of spring migration for High Arctic breeding sanderling Calidris alba using six and eight winter destinations between 55°N and 25°S, respectively. Annual apparent survival was considerably lower for adult birds wintering in tropical West Africa (Mauritania: 0.74 and Ghana: 0.75) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 76 publications
1
47
0
1
Order By: Relevance
“…Few previous studies, however, have been able to directly connect events across seasons with both variation in individual performance and changes in survival rates for migratory species because of the difficulty in tracking individuals throughout their annual cycles and obtaining direct observations of those same individuals at multiple time points during the year (e.g. Reneerkens et al, 2020). In one of the few empirical examples, Gibson et al (2018) were able to link anthropogenic disturbances during the nonbreeding season with reduced body condition and, via reversible state effects, reduced survival and site fidelity in Piping Plovers Charadrius melodus.…”
mentioning
confidence: 99%
“…Few previous studies, however, have been able to directly connect events across seasons with both variation in individual performance and changes in survival rates for migratory species because of the difficulty in tracking individuals throughout their annual cycles and obtaining direct observations of those same individuals at multiple time points during the year (e.g. Reneerkens et al, 2020). In one of the few empirical examples, Gibson et al (2018) were able to link anthropogenic disturbances during the nonbreeding season with reduced body condition and, via reversible state effects, reduced survival and site fidelity in Piping Plovers Charadrius melodus.…”
mentioning
confidence: 99%
“…The factors that determine initial settlement at a nonbreeding site remain unknown but the authors suggest that equatorial sites in West Africa could be an ecological trap if strong site fidelity limits the options for surviving birds to explore or disperse to a better nonbreeding site. Reneerkens et al (2020) confirmed that migration distance entails fitness costs, but quite unexpectedly, they found that the relationships with fitness were nonlinear. One of the great features of their study system was that Sanderlings from different nonbreeding sites stage together at coastal estuaries in Iceland before migrating to Greenland and northern Canada.…”
mentioning
confidence: 84%
“…
In Focus: Reneerkens, J., Versluijs, T. S. L., Piersma, T., Alves, J. A., Boorman, M., Corse, C., … Lok, T. (2020). Low fitness at low latitudes: wintering in the tropics increases migratory delays and mortality rates in an Arctic breeding shorebird.
…”
mentioning
confidence: 99%
“…Juvenile flight feathers of low quality might need to be replaced to retain flying efficiency that allow birds to avoid predators. Migration propensity in yearlings has been shown to be negatively related to migration distance (Fernandez et al 2004, O'Hara et al 2005, Tavera et al 2016, Reneerkens et al 2020. As flight feather wear increases with migration distance, the strategy of returning to breeding grounds retaining juvenile feathers would seem more plausible for shorebirds with shorter migration distances.…”
Section: Role Of Flight Feather Wear and Timing Of Moltmentioning
confidence: 99%